An Error Analysis on Student’s Translation Text - Dina Merris Maya Sari (Makassar State University, 2019)
The ability to translate is a language skill that have to be mastered. A foreign language learner must have the ability to translate both verbally and written. This study aims to describe the level of students’ error in translating text. The qualitative research approach is used to describe the level of students’ error in translating text. The technique of data collection is done in two ways, namely observation and written documents. Data processing includes the activities of identifying and categorizing data, exposuring and interpretating of problems and drawing conclusions. The stage of writing report includes writing report activities and presenting the results. The results show that students make errors in terms of vocabulary, use of prepositions, and incomplete sentences. Error analysis can also be implemented in teaching translation through five stages, namely test, correction, discussion, revision, and evaluation.